Some Geometric Properties of Riesz-Musielak-Orlicz Sequence Spaces: Vakeel A. Khan - Team, Support (Thai Journal of Mathematics, 2010)
The aim of this paper is to calculate Maluta's coe±cient for Riesz-Musielak-Orlicz sequence spaces with the orlicz norm. Furthermore show that Riesz-Musielak-Orlicz sequence space has the Schur's property.